Construction Of Revenue Budget Monitoring Model And Regional Spending Moderated Religiosity - I Made Rian Diana Kartika; Dyah Sawitri; Umi Muawanah (Journal of Social Research, 2024)
This study aims to construct a model of supervision of the Regional Revenue and Expenditure Budget (APBD) consisting of: (1) transparency of public policy affects the supervision of the APBD, (2) public accountability affects the supervision of the APBD, (3) religiosity moderates the transparency of public policy to the supervision of the APBD, (4) religiosity moderates public accountability to the supervision of the APBD. This research was conducted at the Malang City Government DPRD Consultant in 2022. Using explanatory research with a saturated sample technique, as many as 44 council members were obtained, excluding the chairman and researcher. Data related to the research variables were collected through questionnaires given directly to respondents. Furthermore, the data was analyzed by moderation double linear regression. Previously, validity, reliability and classical assumption tests were carried out. The hypothesis was tested using a t-test with a 5% alpa. The results prove that: first, transparency of public policies has a significant positive effect on the supervision of the APBD, second, public accountability has a significant positive effect on the supervision of the APBD, third, religiosity strengthens the influence of public policy transparency on the supervision of the APBD, and fourth, religiosity strengthens the influence of public accountability on the supervision of the APBD.